2023
DOI: 10.1021/acsami.3c04849
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Penetration of CO Molecule into Zeolitic Micropores Almost Plugged by CuCl via π-Complexation of CO-CuCl

Abstract: Carbon monoxide (CO) is a key reactant in several Fischer–Tropsch processes, including those used in light olefin and methanol syntheses. However, it is highly toxic and causes serious poisoning of noble metal catalysts. Thus, a solid adsorbent that can selectively capture CO, especially at low concentrations, is required. In this study, zeolite Y-based adsorbents in which Cu(I) ions occupy the supercage cation sites (CuCl/Y) are prepared via solid-state ion exchange. Volumetric adsorption measurements reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…According to this model, the chemical potential energy in the adsorbed phase is equal to that in the gas phase at equilibrium. Previous literatures have reported that IAST theory was employed to predict the selectivity of copper ion-based adsorbents. , The IAST theoretical calculation formulas are given in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…According to this model, the chemical potential energy in the adsorbed phase is equal to that in the gas phase at equilibrium. Previous literatures have reported that IAST theory was employed to predict the selectivity of copper ion-based adsorbents. , The IAST theoretical calculation formulas are given in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%